A Closer Look on Selected Educational Institution: Are There Any Institutional or Academic Problems? - Dwi Vita Lestari S. (LPPM Universitas Lancang Kuning. Pekanbaru. Indonesia, 2020)
This study aims to identify the management and academic quality problems of Muhammadiyah Tanjungpinang education institutions in the Riau Islands. This research was conducted at schools within the auspices of Muhammadiyah institutional in Eastern Tanjungpinang District. This descriptive study collected data through question and answer sessions in interview sessions with school administrators and managers. The data then triangulate with observation and field notes. The analysis in this study managed to reveal that it seems there are problems and some weaknesses in the management of institutions and academics. It can be seen from the lack of long, medium, and short term implementation programs in carrying out institutional management activities education. However, this problem is a general problem that can be found in many educational institutions around the globe. Therefore. This study sees it urgent to increase human resources with experiences in institutional and academic management to fix existing problems.